2013
DOI: 10.3144/expresspolymlett.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic analysis of inter- and intra-laminar damage in notched PEEK laminates

Abstract: Abstract. This paper presents a finite element model to predict the progressive damage mechanisms in open-hole PEEK (Poly-Ether-Ether-Ketone) laminates. The stochastic laminate's properties with non-uniform stress distribution are considered from element to element using the Gaussian distribution function. The failure modes considered are: fiber tension/ compression, matrix tension/compression, fiber/matrix shear, and delamination damage. The onset of damage initiation and propagation are predicted and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…To calculate and compare the values of the contact pressures caused by the soft-gelatine projectiles and hard aluminium-alloy projectiles, the impact behaviour of the CF/PEEK composite target was modelled. The relevant material properties of the CF/PEEK composites required for the modelling studies may be found from the literature [11,12,15,[48][49][50][51][52][53][54] and are given in Table 4.…”
Section: Modelling Studiesmentioning
confidence: 99%
“…To calculate and compare the values of the contact pressures caused by the soft-gelatine projectiles and hard aluminium-alloy projectiles, the impact behaviour of the CF/PEEK composite target was modelled. The relevant material properties of the CF/PEEK composites required for the modelling studies may be found from the literature [11,12,15,[48][49][50][51][52][53][54] and are given in Table 4.…”
Section: Modelling Studiesmentioning
confidence: 99%
“…Failure initiation and propagation were modelled with Hashin's failure criteria and fracture energy evolution law. In this work, the strength modelling of ROS is developed using failure initiation and propagation methods 20 coupling with the Hashin's failure criteria.…”
Section: Modelling Of Ros Propertiesmentioning
confidence: 99%
“…In this article, fracture energies were chosen so that stressstrain curves of [0/AE60] 3S and [90/AE30] 3S laminates obtained from FE analysis would match the experimental results, as shown in Figure 12. Baseline energy values were taken from the modelling papers, 20,23 which relied on approximate values to model progressive crack growth in open-hole GLARE 23 and CF…”
Section: Failure Criteriamentioning
confidence: 99%
“…Table 1 lists 45 references published between 2008 and 2015 in which this element is used. ABAQUS also offers the 6 node, three dimensional cohesive element COH3D6 to be used with tetrahedral solid elements [204][205][206][207][208] and the 4 node, two-dimensional cohesive element COH2D4 [209][210][211]. Cohesive elements are also available in many commercial finite element programs including LS-DYNA, MSC.Marc and ANSYS [212].…”
Section: Applications Of Cohesive Elementsmentioning
confidence: 99%